2018
DOI: 10.1021/acscatal.8b03331
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Restructuring of Silver Particles during Ethylene Epoxidation

Abstract: The restructuring of a silver catalyst during ethylene epoxidation under industrially relevant conditions was investigated without and with vinyl chloride (VC) promotion. During non-VC-promoted ethylene epoxidation, the silver particles grow and voids are formed at the surface and in the bulk. Electron tomography highlighted the presence of voids below the Ag surface. A mechanism is proposed involving reconstruction of the silver lattice and defect sites induced by oxygen adsorption on the external surface and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…Experimentally, the selectivity of ethylene oxide over clean Ag is about 40%-50%, and its selectivity can be increased to 90% by the accumulation of solid promoters such as alkali metals as well as Re and Mo [27][28][29]. Among numerous experimental studies, van Hoof et al [30] studied the ethylene epoxidation over Ag catalysts by adding selective species, and found that substantial impact of a small amount of impurity on a well-studied heterogeneous catalyzed reaction. These results point to the importance of adding fine-selected "impurity" on improving catalytic reaction performance for ethylene epoxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, the selectivity of ethylene oxide over clean Ag is about 40%-50%, and its selectivity can be increased to 90% by the accumulation of solid promoters such as alkali metals as well as Re and Mo [27][28][29]. Among numerous experimental studies, van Hoof et al [30] studied the ethylene epoxidation over Ag catalysts by adding selective species, and found that substantial impact of a small amount of impurity on a well-studied heterogeneous catalyzed reaction. These results point to the importance of adding fine-selected "impurity" on improving catalytic reaction performance for ethylene epoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various metal oxide supports, polyoxometalate (POM) clusters are heteropolyacid oxoanions that posses considerable stability, well-defined structures, and interesting catalytic properies, thus being a promising support for developing SACs with high stability. The solid POMs possess a separate anionic structure, which is more like a distinct portion of the solid metal oxides [30][31][32][33][34][35][36][37][38][39][40][41]. For many years, POMs have been used as catalyst support materials due to the following advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the coverage, chlorine can: (i) adsorb on surface or penetrate into subsurface at low coverages or (ii) completely poison (via blockage of oxygen chemisorption) the catalyst in case of high-concentration co-feeding [81,86,[88][89][90]. The scenario of formation of highly mobile AgCl species leading to the restructuring and redispersion of Ag particles was also considered in the literature [91]. Interestingly, the replacement of the alumina support (industrially used) by CuO leads to CuO acting as a sponge for low concentrations of chlorine and is accompanied with formation of CuO/ Cl derivatives [92].…”
Section: Promotion By Ethyl Chloridementioning
confidence: 99%
“…Tomography techniques are particularly valuable to the study of both the surface and the bulk structure and composition of catalytic materials. Neutron tomography [1] and X-Ray microtomography [2][3][4] have only been used to a small extent to study catalytic materials due to their lower resolution, but there is growing interests in the study of catalysts by electron tomography [5][6][7] and atom probe tomography [8]. Atom probe tomography is part of the field emission techniques, which comprise the Field Emission Microscopy (FEM), Field Ion Microscopy (FIM) and Atom Probe Tomography (APT).…”
Section: Introductionmentioning
confidence: 99%